2022
DOI: 10.3390/app12052500
|View full text |Cite
|
Sign up to set email alerts
|

The Quality Analysis and Deterioration Mechanism of Liquid Egg White during Storage

Abstract: The quality of liquid egg white (LEW) during storage is critical for the development of the egg industry. In order to effectively control its storage quality, the effects of packaging materials and storage conditions on the quality of LEW were investigated. High-throughput sequencing (HTS) was applied to explore changes in bacterial population proportions and microflora in the spoilage of LEW. The shelf life of LEW packaged with glass (LEW-PG), plastic (LEW-PP), and tinplate (LEW-PT) was preliminarily determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…On the 28th day of storage, the overall appearance, smell, taste, and texture of the eggs were rated lower than on earlier evaluation dates. Furthermore, the results of Guo et al [32] on sen- There was no effect of packaging type on the foaming capacity and foaming stability of egg white foam (Table 4). The foaminess and stability of foam from eggs stored in plastic and cardboard packaging was similar (p > 0.05) at all assessment dates.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…On the 28th day of storage, the overall appearance, smell, taste, and texture of the eggs were rated lower than on earlier evaluation dates. Furthermore, the results of Guo et al [32] on sen- There was no effect of packaging type on the foaming capacity and foaming stability of egg white foam (Table 4). The foaminess and stability of foam from eggs stored in plastic and cardboard packaging was similar (p > 0.05) at all assessment dates.…”
Section: Resultsmentioning
confidence: 87%
“…On the 28th day of storage, the overall appearance, smell, taste, and texture of the eggs were rated lower than on earlier evaluation dates. Furthermore, the results of Guo et al [ 32 ] on sensory evaluation showed that the eggs had satisfactory sensory evaluation results on the first day after laying and deteriorated with increasing storage time. The results of Attia et al [ 34 ], who studied the sensory characteristics of eggs, showed that fresh eggs were superior in quality to eggs stored for 21 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation